Enhancement of Solubility and Improvement of Dissolution Rate of Atorvastatin Calcium Prepared as Nanosuspension - Ahmed H. Ali; Shaimaa N. Abd-Alhammid (College of Pharmacy University of Baghdad, 2019)
Atorvastatin have problem of very slightly aqueous solubility (0.1-1 mg/ml). Nano-suspension is used to enhance it's of solubility and dissolution profile. The aim of this study is to formulate Atorvastatin as a nano-suspension to enhance its solubility due to increased surface area of exposed for dissolution medium, according to Noyes-Whitney equation.         Thirty one formulae were prepared to evaluate the effect of ; Type of polymer, polymer: drug ratio, speed of homogenization, temperature of preparation and inclusion of co-stabilizer in addition to the primary one; using solvent-anti-solvent precipitation method under high power of ultra-sonication. In this study five types of stabilizers (TPGS, PVP K30, HPMC E5, HPMC E15, and Tween80) were used in three different concentrations 1:1, 1:0.75 and 1:0.5 for preparing of formulations. At the same time, tween80 and sodium lauryl sulphate have been added as a co-stabilizer.          Atorvastatin nano-suspensions were evaluated for particle size, PDI, zeta potential, crystal form and surface morphology. Finally, results of particle size analysis revealed reduced nano-particulate size to 81nm for optimized formula F18 with the enhancement of in-vitro dissolution profile up to 90% compared to 44% percentage cumulative release for the reference Atorvastatin calcium powder in 6.8 phosphate buffer media. Furthermore, saturation solubility of freeze dried Nano suspension showed 3.3, 3.8, and 3.7 folds increments in distilled water, 0.1N Hcl and 6.8 phosphate buffers, respectively. Later, freeze dried powder formulated as hard gelatin capsules and evaluated according to the USP specifications of the drug content and the disintegration time.        As a conclusion; formulation of poorly water soluble Atorvastatin calcium as nano suspension significantly improved the dissolution of the drug and enhances its solubility.